Conserved RXLR Effector Genes of Phytophthora infestans Expressed at the Early Stage of Potato Infection Are Suppressive to Host Defense - Yin, Junliang; Gu, Biao; Huang, Guiyan; Tian, Yuee; Quan, Junli; Lindqvist-Kreuze, Hannele; Shan, Weixing (Frontiers in Plant Science, 2017)
Late blight has been the most devastating potato disease worldwide. The causal agent, Phytophthora infestans, is notorious for its capability to rapidly overcome host resistance. Changes in the expression pattern and the encoded protein sequences of effector genes in the pathogen are responsible for the loss of host resistance. Among numerous effector genes, the class of RXLR effector genes is well-known in mediating host genotype-specific resistance. We therefore performed deep sequencing of five genetically diverse P. infestans strains using in planta materials infected with zoospores (12 hours post inoculation) and focused on the identification of RXLR effector genes that are conserved in coding sequences, are highly expressed in early stages of plant infection, and have defense suppression activities. In all, 245 RXLR effector genes were expressed in five transcriptomes, with 108 being co-expressed in all five strains, 47 of them comparatively highly expressed. Taking sequence polymorphism into consideration, 18 candidate core RXLR effectors that were conserved in sequence and with higher in-planta expression levels were selected for further study. Agrobacterium tumefaciens-mediated transient expression of the selected effector genes in Nicotiana benthamiana and potato demonstrated their potential virulence function, as shown by suppression of PAMP-triggered immunity (PTI) or/and effector-triggered immunity (ETI). The identified collection of core RXLR effectors will be useful in the search for potential durable late blight resistance genes. Analysis of 10 known Avr RXLR genes revealed that the resistance genes R2, Rpi-blb2, Rpi-vnt1, Rpi-Smira1, and Rpi-Smira2 may be effective in potato cultivars. Analysis of 8 SFI (Suppressor of early Flg22-induced Immune response) RXLR effector genes showed that SFI2, SFI3, and SFI4 were highly expressed in all examined strains, suggesting their potentially important function in early stages of pathogen infection.